Resiliency enhancement : putting the strengths perspective into social work practice - Norman, Elaine (Columbia University Press, 2000)
This book bridges the gap between theory and implementation to illustrate how resiliency enhancement enables social workers to put the strengths perspective successfully into practice for their clients. Contributors to this volume show how social workers can use interventions to enhance those resiliency factors.